2000
DOI: 10.3168/jds.s0022-0302(00)75158-7
|View full text |Cite
|
Sign up to set email alerts
|

Bias in Genetic Evaluations by Records of Cows Treated with Bovine Somatotropin

Abstract: Records from Dairy Records Management Systems in Raleigh were used to estimate effects of bovine somatotropin (bST) treatment and to predict breeding values for milk production traits. The data comprised 5245 test-day records of bST-treated cows and 126,223 test-day records of untreated cows in first lactation for milk, fat, and protein yields. Fixed effects of bST treatment were estimated from test-day animal models with herd-test-date as another fixed factor. Percentage increases due to bST treatment ranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…Burton et al (1990) reported that bST can enhance milk yields without an apparent effect on mammary gland or general cow health. Collier et al (2001), in a study on the effect of using bST on the health of cows in commercial dairy cattle herds that were chosen randomly from different regions of the United States, showed that health problems in cows treated by bST were the same as Tsuruta et al (2000) reported estimates of heritability of 0.19 and repeatability of 0.39 for milk yield for cows treated with bST.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Burton et al (1990) reported that bST can enhance milk yields without an apparent effect on mammary gland or general cow health. Collier et al (2001), in a study on the effect of using bST on the health of cows in commercial dairy cattle herds that were chosen randomly from different regions of the United States, showed that health problems in cows treated by bST were the same as Tsuruta et al (2000) reported estimates of heritability of 0.19 and repeatability of 0.39 for milk yield for cows treated with bST.…”
Section: Introductionmentioning
confidence: 78%
“…AlJumaah (2001) obtained estimates of heritability of 0.18 and of repeatability of 0.43 for milk yield with bST and of 0.13 and 0.39 for untreated cows. Tsuruta et al (2000) reported estimates of heritability of 0.19 and repeatability of 0.39 for milk yield for cows treated with bST.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MORBECK et al (1991), por sua vez, observaram médias de 8.350 ± 562 kg, 8.348 ± 515 kg, 9.571 ± 515 kg e 9.070 ± 515 kg respectivamente para avaliação de quatro dosagens de aplicação de bST (0 mg, 5,15 mg, 10,3 mg e 16,5 mg). TSURUTA et al (2000) encontraram efeito significativo no tratamento com bST sobre a produção de leite. Neste estudo os autores verificaram que a aplicação deste hormônio elevou a produção em 7,2%.…”
Section: Resultsunclassified